The first-time fathers’ experiences in early fatherhood: a descriptive qualitative study - Nurumal, Mohd Said; Rohim, Muhammad Aiman; Jamaludin, Thandar Soe @ Sumaiyah; Shorey, Shefaly; Noviani, Wulan (IIUM Press, 2024)
Background: Becoming a father is a stressful transition period for men, presenting numerous challenges from caring for their newborns to navigating changes in family dynamics. Recently, cultural expectations have shifted, transforming the role of the father from primarily being a breadwinner to being more actively involved in parenting. There is growing evidence that first-time fathers encounter various obstacles and have unmet needs during the parenting period. Thus, before encouraging fathers in society to take on more active parental roles, it is crucial to gain a comprehensive understanding of their support needs, experiences, and challenges. This study aimed to explore the experiences of the first-time fathers in the early parenthood.